Issues of accuracy in social research findings - Ab. Ghani Hilmi, Zulkifli (Universiti Teknologi MARA, 2009)
Accuracy of research findings is of utmost important in any research. Knowing some statistical procedures and applications of statistical software does not guarantee the quality of the data analysis unless it is founded by some understanding of the underlying theoretical background of the statistical procedures. This paper highlights the areas to be considered at the beginning of conducting a social research that would affect the end results. Getting the right population and a representative sample of the population is the first issue any researcher will face. After data have been collected, they need to be explored to verify certain parametric assumptions, missing values and outliers. Other sources of error are also briefly described.